Clonal analysis of the quasispecies of antiviral-resistant HBV genomes in patients with entecavir resistance during rescue treatment and successful treatment of entecavir resistance with tenofovir - SEVEN, GÜLSEREN; Karatayli, Ersin; Idilman, Ramazan; Karatayli, Senem C.; Cevik, Emrah; Yakut, Mustafa; Seven, GÜLSEREN; Kabacam, Gokhan; Bozdayi, A. Mithat; Yurdaydin, Cihan (My University, 2013)
Background: Clonal analysis of quasispecies of resistant HBV genomes in patients with entecavir (ETV) resistance receiving lamivudine (3TC) plus adefovir (ADV) rescue therapy has never been performed.